Decoration Elements and Symbolic Meanings in Yixing Purple Clay Teapots: A focus on nature-themed decorations - Shi Lijuan1; Siti Maryam Ali Yasin; Zahirah Harun; Li Zhou; Wang Lizhi (Environment-Behaviour Proceedings Journal, 2025)
Yixing purple clay teapots are not merely functional objects but also embody rich cultural significance through their intricate designs. This paper explores the relationship between decoration elements and their symbolic meanings in Yixing pottery. The decoration focuses on nature-themed comprised of 1) flowers, 2) plants, 3) animals, and 4) landscapes. By examining these elements, the paper delves into how they convey deep cultural meanings and impact pottery’s overall perception and value. The findings suggest that these decoration elements are integral to preserving cultural heritage and continue influencing the aesthetic appreciation and market value of Yixing teapots.